Psychological impact of COVID-19 pandemic on medical and paramedical staff at a tertiary care center: an observational, cross sectional, survey-based study - Ramteke, Gunjan; Britto, Namrata; Gawali, Vijaykumar (International Journal Of Community Medicine And Public Health, 2021)
Background: The health-care workers experienced various adverse psychological reactions due to COVID-19 pandemic. We aim to assess the anxiety and stress faced by the medical and paramedical staff while dealing with the pandemic. Methods: Analysis of 190 respondents of the survey was performed. Medical and paramedical staff included those of Bhaktivedanta hospital and research institute, Mumbai only. Data based on two questionnaires GAD-7 and “stress and anxiety assessment scale (SAAS)” was collected in the form of a survey from 15August 2020 till 31 May 2021 to assess the individual’s mental health. Results: Analysis of responses from GAD-7, a 7-item assessment scale and SAAS, a 14-item assessment scale were obtained. From the GAD-7 scale, 3.53% and from the SAAS scale, 9.09%, of the total health-care workers were found to have high anxiety and stress due to the Covid-19 pandemic. Conclusions: Although mediocre levels of stress and anxiety were found to be prevalent among the medical health-care workers, proper and timely mental health support and care must be provided to them even in normal conditions. This ensures safe and efficient execution of one’s duties even during crisis.